Morel berry leaf extract reduce levels of reactive oxygen species and increase levels of endothelial nitric oxide synthase of male Wistar rat exposed to cigarette smoke - Felicia Hartono; Gde Ngurah Indraguna Pinatih; Anak Agung Ayu Ngurah Susraini (Indoscholar, 2021)
Background: Exposure to cigarette smoke increased the level of reactive oxygen species (ROS) and caused oxidative stress which could lead to early aging includes vascular aging. Morel berry leaf contained flavonoid works as antioxidant that neutralized ROS. This study aimed to investigate effectivenes of Morel berry (Physalis angulata L.) leaf extract to decrease levels of ROS and increase levels of endothelial nitric oxide synthase (eNOS) in male Wistar rats exposed to cigarette smoke. Method: This research was an experimental study with pre test-post test control group design. 16 healthy male rats (Rattus norvegicus), Wistar strain, 3-4 months, weight 180-200gr were used, divided randomly into two groups. The control group was given aquadest and the treatment group was given Morel berry leaf extract 500 mg/kgBW/day. Continued to 30 minutes exposed to cigarette smoke. ROS and eNOS levels were measured before and after 28 days treatment, using rat ROS ELISA Kit and rat ENOS ELISA Kit respectively. Results: The results showed that the mean ROS levels in the treatment group decreased significantly and was significantly lower than in control group (75.789 + 3.298 vs 91.646 + 1.970; p < 0.001). The mean eNOS levels in the treatment group increased significantly and was significantly higher than control group (8.597 + 0.375 vs 5.957 + 0.329; p < 0.001). Conclusion: The results of this study indicated that administration of Morel berry leaf extract reduced levels of ROS and increased serum levels of eNOS in male Wistar rats exposed to cigarette smoke.